(untitled) (مجلة المنصور, 2022)
Evaluating the quality of a website helps to assess whether or not the website is meeting its intended purpose for the intended users. Besides, the results of the evaluation can help to understand the parts of the website that need modifications to bring an improvement in the website. Usability is one of the most important quality factors in any quality model for the website. In this paper a Website Usability Model (WUM) for informational websites from developer perspective was designed and implemented, an extensive study of the literature on existing quality models, essential website success factors and criteria was made to identify necessary quality characteristics, sub- characteristics and criteria. The proposed WUM able to evaluates the usability of academic websites automatically online and makes a suggestion according to the results. It includes four layers browsing layer, parsing layer, evaluation layer and suggestion layer. The experimental results showed that the WUM able to make a decisions such that some websites in general have a good scale of usability, while other websites having defects in the usability be revisited using the WUM suggestions.